34 Post-injury psychological symptoms: differences between concussions and orthopaedic injuries. (9th June 2015) - Yang, Jingzhen (Ginger); Coxe, Kathryn; Singichetti, Bhavna; Ramirez, Marizen; Peek-Asa, Corinne
Abstract : Statement of purpose: This study examined differences in post-injury psychological symptoms between collegiate athletes who sustained concussions and orthopaedic injuries. Method: A cohort of athletes was recruited at the beginning of each sports season from 2007 to 2011. Study participants were collegiate athletes from 9 sports teams at two Big Ten Conference universities. Upon injury, injured athletes were followed prospectively at multiple intervals to measure psychological symptoms (e.g., 1 week, and 1, 3, 6, and 12 months) until the injured athlete's return to play. Differences in post-injury psychological symptoms, including symptoms of depression and anxiety, pain, fear of re-injury, and fear of return-to-play were compared between athletes with concussions and orthopaedic injuries, both at one week after injury and at return-to-play. Results: Of a total of 597 injuries sustained, 71 (11.9%) were concussions and 526 (88.1%) were orthopaedic injuries. One-fourth of concussions (n = 18, 25.4%) were sustained by females. Football had the largest number of concussions (n = 42) and orthopaedic injuries (n = 196). No differences in post-injury symptoms of depression and anxiety were found between athletes with concussions and orthopaedic injuries. While 88.7% of concussed athletes returned to play one week following injury, only 59.1% of athletes with orthopaedic injuries did so. Furthermore, concussed athletes were less likely to report pain (p < 0.0001), fear of re-injury (p < 0.0001), and fear of return-to-play (p < 0.0001) at one week following injury, than athletes with orthopaedic injuries. These differences remained significant at return-to-play as well as after adjusting for covariates. Conclusions: While post-injury psychological symptoms are often not evident for concussed athletes, these symptoms need to be addressed to ensure successful injury recovery. Significance and contributions: Our findings provide empirical evidence on differences in psychological symptoms between athletes with concussions and orthopaedic injuries, and have practical implications for psychological recovery from injuries.